Perturbations to Saturn's F-ring strands at their closest approach to Prometheus - Giuliatti Winter, S. M. [UNESP]; Murray, C. D.; Gordon, M. (Elsevier, 2000)
The strange morphology of the F ring of Saturn is thought to be caused by the perturbing effects of two close satellites, Prometheus and Pandora. The F ring and the satellites also experience periodic close encounters as a result of differential precession arising from Saturn's oblateness. Using the orbits of the F-ring strands derived by Murray et al. (1997, Icarus 129, 304-316) the behaviour of the ring particles at their closest approach to Prometheus is analysed using numerical simulations. The results show that a gap and a wave are formed in the ring at each encounter with the satellite. However, the gap is expected to have a short lifetime due to keplerian shear. © 2000 Elsevier Science Ltd. All rights reserved.